Diversity and relative abundance of Order Lepidoptera from agro-ecosystem of District Sialkot, Pakistan (Zoo Botanica, 2025)
Moths, skippers, and butterflies are all members of the second most well-known and diverse order of insects, the order Lepidoptera. In agronomic domains, lepidopterans are ecologically important insects that serve as both pollinators and pests. Agro-ecosystems support a diverse range of pests and beneficial insects. Agro-ecosystems support a diverse range of pests and beneficial insects. During the current study, the diversity and relative abundance of Lepidopteran species (including both adults and larvae) were analyzed from the selected crops i.e. fodder, brassica, wheat, and vegetables from agro-ecosystems of district Sialkot, Pakistan. Sampling was done through the quadrat and sweep net methods from March 2021 to June 2021. A total of 2013 Lepidopteran specimens constituting 26 genera and 29 species belonging to 10 families were recorded from these crops available at the selected locales of Sialkot district. The fodder crop was found to be rich in Lepidopterans manifesting a relative abundance of 53.40% followed by brassica (25.88%), vegetables (19.82%), and least was in wheat (0.89%). Maximum relative abundance was noticed in May (33.48%) followed by April (31.84%), March (20.07%), and lowest in June (14.61%). Family Pieridae was the most abundant family with a relative abundance of 41.03% followed by the family Noctuidae (39.29%). The most dominant species was Helicoverpa armigera showing a relative abundance of 17.44%. The fodder crop (H’= 2.999) and the month of May (H’=2.8053) demonstrated the highest diversity among all the data evaluated by the Shannon-Weiner diversity index (H’). It is concluded that district Sialkot has a diversified Lepidopteran fauna. For the purpose of assessing their diversity, abundance, and distribution in upcoming conservation and pest management research, the current study may assist in identifying beneficial Lepidopteran species and pests in agro-ecosystems.
Keywords: Lepidoptera; relative abundance; quadrat; sweep net; shannon weiner diversity index